Introduction to Accounting and Finance - KAMILAH AHMAD; SHAFIE MOHAMED ZABRI (2023)
This book provides a brief description of the basis of business financial management. The contents are developed in accordance with the needs of university students who are not majoring in accounting or finance as well as for anyone who needs fundamental information related to accounting and finance. In summary, this book covers the basic concepts and principles of financial accounting, double-entry system, adjusting and closing entries, financial statements preparation and assessment, introduction to finance and financial management, time value of money, capital budgeting technique and working capital management. This book aims to help anyone who wants to read and interpret the financial information of an organisation for improving the quality of financial-related decision making.